The relationship between neuroticism and mobile phone use among college students in love: The masking effect of self-emotional assessment - Chen, Weijing; Wang, Xiaoqian; Sun, Shan; Liu, Qian; Guo, Zhiwen (Frontiers in Psychology, 2022)
The relationship between neuroticism and mobile phone use is a hot research topic in the academic community. The purpose of this study was to investigate the roles of self-emotional assessment and love status in the mechanism through which college students’ neuroticism influences mobile phone use.We construct a moderated mediation model, and taking 869 Chinese college students as the research object, testing the mediating role of self-emotional assessment and the moderating role of love status. The results show that: (1) neuroticism was significantly positively related to mobile phone use and significantly negatively related to self-emotional assessment; self-emotional assessment was significantly positively related to mobile phone use; (2) self-emotional assessment had a masking effect on the relationship between neuroticism and mobile phone use; (3) love status not only moderated the relationship between self-emotional assessment and mobile phone use, but also moderated the process through which self-emotional assessment masked the effect of neuroticism on mobile phone use. Our research expands the literature on the mechanisms underlying the effects of neuroticism on mobile phone use, enriches the understanding of the pertinent boundary conditions, and provides a better explanatory basis for the mobile phone use of college students.